Effect of medroxyprogesterone acetate on thyrotropin secretion in adult and old female rats - Moreira,R.M. (2000)
Steroid hormones have been implicated in the modulation of TSH secretion; however, there are few and controversial data regarding the effect of progesterone (Pg) on TSH secretion. Medroxyprogesterone acetate (MPA) is a synthetic alpha-hydroxyprogesterone analog that has been extensively employed in therapeutics for its Pg-like actions, but that also has some glucocorticoid and androgen activity. Both hormones have been shown to interfere with TSH secretion. The objective of the present study was to investigate the effects of MPA or Pg administration to ovariectomized (OVX) rats on in vivo and in vitro TSH release and pituitary TSH content. The treatment of adult OVX rats with MPA (0.25 mg/100 g body weight, sc, daily for 9 days) induced a significant (P<0.05) increase in the pituitary TSH content, which was not observed when the same treatment was used with a 10 times higher MPA dose or with Pg doses similar to those of MPA. Serum TSH was similar for all groups. MPA administered to OVX rats at the lower dose also had a stimulatory effect on the in vitro basal and TRH-induced TSH release. The in vitro basal and TRH-stimulated TSH release was not significantly affected by Pg treatment. Conversely, MPA had no effect on old OVX rats. However, in these old rats, ovariectomy alone significantly reduced (P<0.05) basal and TRH-stimulated TSH release in vitro, as well as pituitary TSH content. The results suggest that in adult, but not in old OVX rats, MPA but not Pg has a stimulatory effect on TSH stores and on the response to TRH in vitro.